The Influence of Artistic Kitsch on the Formation of Political Memes - Anastasiia Tormakhova; Dmytro Tovmash; Ruslan Grechkosii (ESPES)
Memes are an integral part of the digital culture of the globalisation era. Being a powerful form of communication, they have a large audience and influence on society. Their origin was due to the emergence of kitsch and its spread in 20th century culture and art. It was kitsch, which went from ‘low’ art to camp, that initiated the spread of visual forms that perform a powerful communication function. Political memes have an ideological and relaxation function, and they have a pronounced comic element. A correlation can be traced between them and kitsch, which can be the subject of interdisciplinary research.